I would like to express the product $$ \left( \sum_{k \in \mathbb{Z}} a_k \sin(k t) \right) \left( \sum_{k \in \mathbb{Z}} b_k \cos(k t) \right) $$ as $$ \sum_{k \in \mathbb{Z}} c_k \sin(k t). $$ Question : How can I express the coefficients $c_k$ as functions of $a_k$ and $b_k$ ? I know that when multiplying two $\cos$ series, for example, the $c_k$ are standard convolution products. I believe using complex exponentials, Cauchy products and the formulae for Fourier coefficients might be useful, but I can't quite see how to proceed.

  • 3
    $\begingroup$ Use the fact that $2 \sin(kt)\cos(k't) = \sin((k+k')t) + \sin((k-k')t)$ $\endgroup$ – user10676 Jun 2 '14 at 14:47

Let's assume without loss of generality the the indices for the sine series are positive and the ones of the cosine series are non-negative:

$$x(t)=\sum_{k=1}^{\infty}a_k\sin(kt),\quad y(t)=\sum_{k=0}^{\infty}b_k\cos(kt)$$

Rewrite $x(t)$ as

$$x(t)=\frac{1}{2i}\sum_{k=1}^{\infty}a_k(e^{ikt}-e^{-ikt})= \frac{1}{2i}\left(\sum_{k=1}^{\infty}a_ke^{ikt}-\sum_{k=-\infty}^{-1}a_{-k}e^{ikt}\right)=\\=\sum_{k=-\infty}^{\infty}d_ke^{ikt},\quad d_k=\begin{cases}\frac{a_k}{2i},&k>0\\0,&k=0\\-\frac{a_{-k}}{2i},&k<0\end{cases}$$

Note that the coefficients $d_k$ are purely imaginary and satisfy $d_k=-d_{-k}$. In a completely analogous way we can write $y(t)$ as

$$y(t)=\sum_{k=-\infty}^{\infty}f_ke^{ikt},\quad f_k=\begin{cases}\frac{b_k}{2},&k>0\\b_0,&k=0\\\frac{b_{-k}}{2},&k<0\end{cases}$$

Now we can express $z(t)=x(t)y(t)$ as




Note that $g_k$ is purely imaginary and satisfies $g_k=-g_{-k}$ and $g_0=0$. So we can rewrite $z(t)$ as


Note that the final coefficients $2ig_k$ are of course real-valued.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.